2019
DOI: 10.21093/di.v19i2.1553
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Self-efficacy and Creative Thinking at Writing Skill Learning

Abstract: Self-efficacy is a person's belief in his ability to solve planned activities.  Self-efficacy reflects a person’s confidence in their ability to perform tasks creatively and optimistically. The elements to Self-efficacy are mastery experience, vicarious experience, social persuasion, affecative physiological states. Creative thinking is ability to find new ideas originally that are surprising to define it, and also valuable in sensitivity, and the factors are fluency, flexibility, originality, sensitivity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In relation to the research question, the result of the research does not support previous research that found that writing and self-efficacy are correlated (Anam & Stracke, 2020;Deviana et al, 2019;Hetthong & Teo, 2013;Rahimpour & Jahan, 2011;Singh & Rajalingam, 2012;Weda, 2018). This study did not have enough evidence to reject the null hypothesis and to prove that the alternative hypothesis is true.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In relation to the research question, the result of the research does not support previous research that found that writing and self-efficacy are correlated (Anam & Stracke, 2020;Deviana et al, 2019;Hetthong & Teo, 2013;Rahimpour & Jahan, 2011;Singh & Rajalingam, 2012;Weda, 2018). This study did not have enough evidence to reject the null hypothesis and to prove that the alternative hypothesis is true.…”
Section: Discussioncontrasting
confidence: 88%
“…However, research in correlational study on writing self-efficacy and writing performance show a conflicting finding. Some research proposes that there is correlation between writing and self-efficacy (Anam & Stracke, 2020;Deviana et al, 2019;Hetthong & Teo, 2013;Rahimpour & Jahan, 2011;Singh & Rajalingam, 2012;Weda, 2018;Basaffar & Alzahrani, 2022), while other research shows different result (Khojasteh, Shokrpour, & Afrasiabi, 2016;Aldina, 2022). This present study is intended to investigate whether there is indeed a correlation between writing self-efficacy and writing performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kolb (Kolb & Kolb, 2005), there are four learning styles. These are the transforming style based on reflective observation and concrete experiences, the assimilating style based on reflective observation and abstract conceptualization, the decomposing style based on abstract conceptualization and active life, and the locating style based on active life and concrete life (Atiker et al, 2021;Bakaç, 2022;Mohiuddin, 2021;Ciancarini et al, 2020;Deviana et al, 2019;Daud et al, 2016).…”
Section: A Introductionmentioning
confidence: 99%
“…Self-efficacy could be a person's belief in his ability to resolve planned activities. Self-efficacy reflects a person's confidence in their ability to perform tasks creatively and optimistically (Deviana at al., 2019). Students with high and sufficient self-efficacy can be more comfortable and productive when faced with studies with high difficulty levels.…”
Section: A Introductionmentioning
confidence: 99%